Y665F variant of mouse Stat5b protects against acute kidney injury through transcriptomic shifts in renal gene expression - Jakub Jankowski; Hye Kyung Lee; Lothar Hennighausen (Scientific Reports)
Abstract The impact of single nucleotide polymorphisms (SNP) on physiology is often underestimated. One amino acid change can result in a variety of phenotypes apparent only in response to disease or injury. Even known pathogenic SNPs have widespread effects that are currently unaccounted for. In this study, we investigated the impact of the known activating and pathogenic Stat5b Y665F mutation in a renal injury context in mice carrying this variant. Using ischemia–reperfusion model of acute kidney injury, immunohistochemistry, RNA-seq and ChIP-seq, we establish the protective role of STAT5b activation in renal epithelium and showcase the shifts in transcriptomic landscape in a tissue not associated with the usual human phenotype of the STAT5B Y665F mutation. Our data indicate new links between the JAK/STAT pathway and known kidney injury markers, contribute to the understanding of the sexual dimorphism of renal disease, and provide new potential targets for JAK inhibitor- and amino acid transport modulation-based therapies.